Penerapan Customer Relationship Management (CRM) Berbasis Website Terhadap Penilaian Pelanggan - Era Era Hia; Muhammad Khaidir Fahram; Siti Nurhasanah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
reduce customer turnover or departure to other competitors. CRM system at PT. Wingoh Albinda still uses semi-computerization, namely Microsoft excel in managing its data, causing several problems in terms of late service, the response to customers is not optimal. This study presents an analysis of web-based CRM development on a marketing information system at PT. Wingoh Albinda. The result is a web-based CRM system that can manage customer data, product promotions, product sales data and customer service management which is used to store customer inquiries, complaints and ratings to create good relationships with customers. This system is expected to maintain good relations with customers.